BDNF Modulation by microRNAs: An Update on the Experimental Evidence - De Assis, Gilmara Gomes [UNESP]; Murawska-Ciałowicz, Eugenia (MDPI, 2024)
MicroRNAs can interfere with protein function by suppressing their messenger RNA translation or the synthesis of its related factors. The function of brain-derived neurotrophic factor (BDNF) is essential to the proper formation and function of the nervous system and is seen to be regulated by many microRNAs. However, understanding how microRNAs influence BDNF actions within cells requires a wider comprehension of their integrative regulatory mechanisms. Aim: In this literature review, we have synthesized the evidence of microRNA regulation on BDNF in cells and tissues, and provided an analytical discussion about direct and indirect mechanisms that appeared to be involved in BDNF regulation by microRNAs. Methods: Searches were conducted on PubMed.gov using the terms “BDNF” AND “MicroRNA” and “brain-derived neurotrophic factor” AND “MicroRNA”, updated on 1 September 2023. Papers without open access were requested from the authors. One hundred and seventy-one papers were included for review and discussion. Results and Discussion: The local regulation of BDNF by microRNAs involves a complex interaction between a series of microRNAs with target proteins that can either inhibit or enhance BDNF expression, at the core of cell metabolism. Therefore, understanding this homeostatic balance provides resources for the future development of vector-delivery-based therapies for the neuroprotective effects of BDNF.
Keywords: BDNF; microRNA; neuroprotection; regenerative medicine